The Archaeological Guide to Iowa - Whittaker, William E., 1971- (Book collections on Project MUSE., 2015)
Iowa has the reputation of being one big corn field, so you may be surprised to learn it boasts a rich crop of recorded archaeological sites as well-approximately 27,000 at last count. Some are spectacular, such as the one hundred mounds at Sny Magill in Effigy Mounds National Monument, while others consist of old abandoned farmsteads or small scatters of prehistoric flakes and heated rocks. Untold numbers are completely gone or badly disturbed-destroyed by plowing, erosion, or development. Fortunately, there are many sites open to the public where the remnants of the past are visible, either in their original location or in nearby museum exhibits. Few things are more inspiring than walking among the Malchow Mounds, packed so tightly it is hard to tell where one ends and the other begins. Strolling around downtown Des Moines is a lot more interesting when you are aware of the mounds, Indian villages, and the fort that once stood there. And, although you can't visit the Wanampito site, you can see the splendid seventeenth-century artifacts excavated from it at Heery Woods State Park. For people who want to experience Iowa's archaeological heritage first hand, this one-of-a-kind guidebook shows the way to sixty-eight important sites. Many are open to visitors or can be seen from a public location; others, on private land or no longer visible on the landscape, live on through artifact displays. The guide also includes a few important sites that are not open to visitors because these places have unique stories to tell. Sites of every type, from every time period, and in every corner of the state are featured. Whether you have a few hours to indulge your curiosity or are planning a road trip across the state, this guide will take you to places where Iowa's deep history comes to life.